Detection of heavy metal ions in solution using surface plasmon resonance optical sensor - Yap, Wing Fen (2012)
The sensitive, selective and cost-effective method for detection of heavy metal ions in solution is very important in environmental application. Therefore in this study, surface plasmon resonance (SPR) optical sensor has been proposed as an alternative for detection of heavy metal ions (Hg2+, Cu2+, Pb2+, Zn2+ and Mn2+) in solution by developing a chitosan based active layer. The optical properties of heavy metal ions were studied using Kretchmann SPR technique, where gold thin film was used as the interface. Both real and imaginary part of refractive index of the heavy metal ions solution increased with the concentration. This result reveals the basic idea such that SPR can be used to detect heavy metal ions in solution. In order to enhance the sensitivity for SPR in sensing these heavy metal ions, a thin chitosan based active layer is introduced. The chitosan solution was synthesized by homogeneous reaction of medium molecular weight chitosan in aqueous acetic acid solution with glutaraldehyde as crosslinking agent. It was deposited on the gold layer by spin coating. The optical properties of the chitosan active layer before and after contacting with different concentration of heavy metal ions ranging 0.5 to 100 ppm were studied by fitting the experimental results to theoretical data. The results also show that the shift of resonance angle is directly proportional to the concentration of all heavy metal ions solution. The sensitivity of this heavy metal ions optical sensor is in the range of 10–3 ˚ ppm–1, which follows the order: Hg2+ > Cu2+ > Pb2+ > Zn2+ >Mn2+. In this case, the gold/chitosan interface in SPR technique is sensitive with detection limit of 0.5 ppm. The kinetic behaviour of the heavy metal ions on the surface of gold/chitosan was studied by monitoring the self-assembling process in real time. The shift of resonance angle was found to increase exponentially with time, for all concentration of heavy metal ions in the range of 0.5 to 100 ppm, and reach to a saturation value. At low concentration (5 ppm and below), the kinetic reaction is complete in about 100 s. A more complex kinetic profile was observed and complete at approximately 500 s for higher concentration (more than 5 ppm). It is difficult to detect a specific heavy metal ion optically since all heavy metal ions solution are transparent and have similar refractive index when they are at low concentration. Therefore, the modification of the active layer was investigated so that it can selectively detect a specific heavy metal ion and also increase the sensitivity of the detection. The immobilization of p-tert-butylcalix[4]arene-tetrakis in the chitosan thin film has been used. In this case, Pb2+ can be selectively detected with increased sensitivity of 0.045˚ ppm–1 and detection limit has been improved down to 0.03 ppm. The immobilization of tetrabutyl thiuram disulfide in chitosan as active layer gives the selective detection of Zn2+ with sensitivity of 0.032˚ ppm–1 and detection limit of 0.1 ppm.